A watermarking scheme for relational databases with categorical data - Hương, Lưu Bích; Hồng, Bùi Thế (Journal of Computer Science and Cybernetics, 2013)
<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: VI; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">Watermarking is one of the effective measures for copyright protection and the integrity<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;"> <span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: VI; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">of the relational database in the Internet environment. In this paper, we propose a new watermarking scheme which can detect and localize<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;"> <span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: VI; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">the tampering of the relational database with categorical data. This watermarking scheme does not<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;"> <span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: VI; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">change any value in the database, but only changes <span lang="EN-US" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">secretly and securely <span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: VI; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">the order of the tuples in the database.<span lang="VI" style="font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: VI; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-size: 14.0pt;">